Active involvement of children aged 11–12 years in the development of a healthy nutrition intervention – a qualitative evaluation from researchers’ and children’s perspectives - Hannah Jilani; Imke Schilling; Ansgar Gerhardus; Urte Klink (BMC Public Health)
Abstract Background The active involvement of target groups is gaining increasing recognition in health research. Children, in particular, have unique needs and perspectives that differ significantly from those of adult researchers, making their participation essential for improving the relevance and quality of research. Moreover, actively involving children fosters their empowerment. To advance this field, the generation of new knowledge and the refinement of methodologies are crucial. While previous studies have often engaged children with specific health conditions there remains a lack of research evaluating the involvement of healthy children, particularly in terms of process. Therefore, this study aims at answering the two following research questions: (1) What are the barriers and facilitators from the researchers’ perspective when involving healthy children in research? and (2) How do children perceive their active involvement in developing a healthy nutrition intervention in Germany? Methods From September 2023 to January 2024, an intervention to promote healthy nutrition was collaboratively developed with 15 healthy children aged 11 to 12 years and two researchers as part of a school activity group. The process began with joint discussions to clarify goals and roles. Intervention components were developed collaboratively with the children. Researchers documented the process through personal minutes and post scripts, which were analysed to identify barriers and facilitators across three phases: ‘Initiating the process’, ‘Building relationships and defining aims’, and ‘Collaboration process’. Additionally, a child-friendly, semi-structured focus group discussion was conducted to evaluate the process, with the data analysed narratively. Results The researchers’ protocols and postscripts identified both barriers and facilitators across all phases. Overall, the process demanded considerable openness and flexibility from both children and researchers. Establishing shared goals and clarifying roles was time-consuming, and balancing differing expectations without causing disappointment to any of the group proved challenging. Nevertheless, the focus group showed that children enjoyed the project, appreciated the relaxed after-school setting, and valued the interactive approach. They reported learning a lot but expressed disappointment over the limited hands-on activities, such as food preparation, which they had anticipated. Conclusions The evaluation of children’s active involvement highlighted the importance of clear expectation management for successful collaboration. This requires time, openness, and flexibility from all participants. The findings provide practical insights for researchers, supporting the effective involvement of children while reducing potential barriers in future projects.